Effect of irrigation solutions on the coronal discoloration induced by mineral trioxide aggregate cements containing different radiopacifiers - Noushin Shokouhinejad; Marzieh Alikhasi; Mehrfam Khoshkhounejad; Asma Pirmoazen (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to assess the discoloration of coronal tooth structure irrigated with different irrigation solutions and filled with calcium silicate-based materials containing bismuth oxide or calciumzirconia complex as radiopacifier. Materials and Methods: In this ex vivo study, 72 bovine enamel-dentin blocks were prepared and divided into three groups. The dentinal cavities in each group were irrigated with 5.25% sodium hypochlorite (NaOCl), 2% chlorhexidine (CHX), or normal saline for 30 min. After that, irrigation solutions were removed using a cotton pellet. Each group was then randomly divided into two subgroups according to the cavity-filling materials (ProRoot mineral trioxide aggregate [MTA] and RetroMTA). The color assessments were performed before filling the cavities and 1 month and 6 months after filling the cavities. Data were analyzed with two-way ANOVA. The level of statistical significance was set at P < 0.05. Results: The effect of irrigation solution on the color change of calcium silicate-based materials was not statistically significant at none of the time intervals (P = 0.334 and P= 0.252, respectively, for ProRoot MTA and RetroMTA). ProRoot MTA caused a significantly higher color change compared with RetroMTA exposed to different irrigation solutions at each time interval (P < 0.001). Color change of both materials exposed to each irrigation solution significantly increased over time (P < 0.05). Conclusion: Under the condition of this ex vivo study, irrigation of dentin with NaOCl and CHX and then removing the excess solution might be ineffective in increasing the tooth color change potential of either bismuth oxide or zirconium-containing calcium silicate-based materials. Furthermore, calcium silicate-based material, which contained bismuth oxide, caused higher tooth discoloration.